Exploring the Role of Spiritual and Emotional Bonds in Islamic Marriage: A Study of Psychological and Legal Perspectives for Family Sustainability - Firmansyah; Rajab, Khairunnas; Arisman; Lastfitriani, Hellen; Misraini, Irda (Universitas Islam Negeri Raden Intan Lampung, 2026)
As a triadic ethical vocabulary in Islamic family thought, sakinah functions as the telos of marital calm and psychological safety, mawaddah as the affective–commitment dimension of enduring love, and rahmah as the moral–empathic capacity for mercy that enables reconciliation, resilience, and mutual flourishing. This study interrogates how this spiritual–emotional architecture constitutes the substantive core of Islamic marriage beyond its formal-legal contract and clarifies how it may be operationalised to strengthen family sustainability in contemporary settings. Using a library-research design, the article undertakes systematic documentary analysis of primary Islamic sources (the Qur’an, Hadith, and classical fiqh on munākaḥāt) alongside selected contemporary scholarship on marital psychology; the materials are analysed through a descriptive–analytical strategy and a comparative–critical reading that bridges Islamic normative reasoning with relational-psychological constructs (e.g., attachment and emotional intelligence). The synthesis indicates that sakinah–mawaddah–rahmah provides a coherent normative framework for sustaining intimacy, ethical communication, and reconciliation-oriented conflict management, thereby supporting couple resilience over time. At the same time, the analysis identifies a persistent gap between normative ideals and lived marital dynamics, particularly the gendered distribution of emotional and spiritual labour that can undermine relational equity and long-term stability when unaddressed. This study contributes an interdisciplinary conceptual framework integrating Islamic family jurisprudence, marital psychology, and gender-sensitive analysis to inform more relationally grounded premarital education, marital counselling, and policy-oriented discussions on family well-being.